Characteristics of Thyroid Carcinoma Patients in the Inpatient Department of Dr. Mohammad Hoesin General Hospital from January 2020 to December 2022 - Arisa Putri, Amira Azra; Indra, Bima; Qodir, Nur (Indonesian Journal of Cancer, 2025)
Background: Thyroid carcinoma is the most common endocrine malignancy with a rising prevalence. Understanding patients’ sociodemographic characteristics is crucial for improving diagnosis and management. This study aims to provide information about the characteristics of thyroid carcinoma patients.Method: This cross-sectional study analyzed medical records of patients diagnosed with thyroid carcinoma in the Inpatient Department of Dr. Mohammad Hoesin General Hospital, from January 2020 to December 2022. Data collected included age, gender, residence location, main complaints, histopathological variant, disease stage at diagnosis, past medical history, family history, radiation exposure, and type of surgical intervention.Results: Most patients were aged 50-59 years (26.1%) and female (78.3%). The majority came from lowland (90.6%) and rural areas (64.5%). The most common main complaint was a neck lump (63.0%). Papillary thyroid carcinoma was the most frequent variant (87.7%). Most patients were diagnosed at stage I (37.7%), and most patients underwent total thyroidectomy (84.1%). The most common past medical condition was goiter (76.8%). Additionally, 93.5% of patients had no family history of malignancy, and none had radiation exposure. Conclusion: Thyroid carcinoma patients at Mohammad Hoesin General Hospital are predominantly females aged 50-59 from lowland and rural areas. Most were diagnosed with Papillary Thyroid Carcinoma at the early stages and underwent total thyroidectomy.